Pengaruh Strategi Promosi Melalui Media Sosial terhadap Keputusan Pembelian Produk DRW Putri - Bustami, Bustami; Am, Andri Nofiar; Hutasoit, Agnes Monica Febrianti (Jurnal EMT KITA, 2026)
The rapid development of information technology has transformed marketing practices, including those in the skincare industry. This study aims to examine the influence of social media promotional strategies on consumer purchasing decisions for DRW Putri products in Bengkalis. The research uses a quantitative approach with a questionnaire as the primary data collection tool, involving 100 respondents selected through purposive sampling. Data analysis was conducted using validity, reliability, and t-tests. The findings reveal that the social media promotion strategy signifi-cantly and positively influences purchasing decisions, with a contribution level of 27.5% (t = 6.099 > 1.986; sig = 0.000 < 0.05). The results highlight that optimizing social media promotion is crucial to improving consumer purchasing decisions and sustaining competitiveness in the skincare market.
Keywords: Social Media; Promotional Strategy; DRW Putri; Bengkalis Community